Challenges to Implementing Opioid Substitution Therapy in Ukrainian Prisons: Personnel Attitudes Toward Addiction, Treatment, and People With HIV/AIDS - Polonsky, Maxim (Drug Alcohol Depend, 2014)
BACKGROUND: Ukraine is experiencing one of the most volatile HIV epidemics globally, fueled primarily by people who inject drugs (PWIDs), and a parallel incarceration epidemic. Opioid substitution therapy (OST) is internationally recognized as one of the most effective forms of treatment for opioid dependence and is among the most effective HIV prevention strategies available, yet efforts to adopt it in Ukraine’s Criminal Justice System (CJS) have been thwarted. METHODS: To understand the reluctance of the Ukrainian CJS to adopt OST despite the overwhelming evidence pointing to its health benefits and improved criminal justice outcomes, we conducted the first survey of Ukrainian prison administrative, medical and custodial staff (N=243) attitudes towards addiction in general, OST, and people living with HIV/AIDS (PLWHA) in representative regions of Ukraine. RESULTS: Results revealed that Ukrainian CJS workers’ attitudes toward OST, PLWHA, and drug addiction were universally negative, but differed substantially along geographic and occupational lines. Whereas geographic and cultural proximity to the European Union drove positive attitudes in the west, in the southern region we observed an identifiability effect, as workers who worked directly with prisoners held the most positive attitudes. We also found that knowledge mediated the effect of drug intolerance on OST attitudes. CONCLUSION: In Ukraine, adoption of OST is more influenced by ideological biases and prejudices than by existing scientific evidence. By elucidating existing attitudes among CJS personnel, this assessment will help direct subsequent interventions to address the barriers to implementing evidence-based HIV prevention treatments.